AIDS-trauma and politics American literature and the search for a witness - Pozorski, Aimee L. (Aimee Lynn) (Politics, literature, & film., 2019)
"This book revisits representations of AIDS in the 1980s in the U.S. in order to highlight a discourse of trauma and witness that emerged in the wake of a crisis. The book also emphasizes the potential of literary language to call attention to historical trauma where other discourses may fail"--